Strategies of fair lexicography - how present- day dictionaries of English show respect - Garibyan, Armine; Koroleva, Daria; Mittmann, Brigitta; Herbst, Thomas (Lexicographica, 2022)
This article investigates the ways in which present-day monolingual dictionaries of the English language show respect towards groups of people. On the basis of the analysis of selected entries of the most recent editions of English learners' dictionaries and the Concise Oxford Dictionary we outline five different strategies employed in these dictionaries to avoid discrimination of and offensiveness towards other people. The analysis comprises the phrasing of definitions, illustrations, the selection of examples, the choice of headwords as well as usage notes in comparison to data obtained from English corpora.
CRIS-Team WoS Importer:2022-12-30